The Influence of Imported Orange Attributes on Purchase Decision in the Largest Local Orange Production Area in Indonesia - Ramadhan, Aditya Willy; Setiawan, Budi; Cahyono, Edi Dwi; Permana, Adi Indra (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: In E.ast Java Province., the. consumption of importe.d orange.s continue.s to rise., alongside. the. availability of local products in the. marke.t. De.spite. the. ofte.n highe.r price. of importe.d orange.s, many consume.rs still pre.fe.r importe.d orange.s ove.r local one.s. This phe.nome.non sugge.sts that ce.rtain factors influe.nce. the. de.cision to purchase. importe.d orange.s, such as product quality, price., packaging, and the. e.nvironme.nt. This study aims to analyze. the. impact of the.se. variable.s on the. de.cision to purchase. importe.d orange.s in E.ast Java, with purchase. inte.ntion as a me.diating variable.. It is e.xpe.cte.d that the. findings of this re.se.arch can provide. insights into the. factors driving consume.rs to choose. importe.d orange.s and offe.r re.comme.ndations for busine.ss actors to e.nhance. the. compe.titive.ne.ss of local orange.s in the. dome.stic marke.t.Methodology: The. targe.t re.sponde.nts in this study are. the. pe.ople. of E.ast Java who consume. importe.d orange.s. The. se.le.ction of re.sponde.nts is base.d on spe.cific crite.ria that must be. me.t. A total of 327 re.sponde.nts are. involve.d in this study. In this re.se.arch, re.sponde.nts will be. provide.d with a que.stionnaire. containing que.stions with a 1-5 scale. re.late.d to the. re.se.arch be.ing conducte.d. This study will use. two type.s of data colle.ction: primary data and se.condary data. The. colle.cte.d data will be. proce.sse.d using the. SE.M-PLS analysis me.thod with the. Warp-PLS 8.0 software..Finding: The. re.sults of the. study show that product quality, price., packaging, and social e.nvironme.nt have. a positive. and significant e.ffe.ct on the. purchasing de.cision of importe.d orange.s in E.ast Java through purchase. inte.ntion as a me.diating variable., with an R-square. value. of 0.627. This value. indicate.s that the.se. four variable.s are. able. to e.xplain 62.7% of the. purchasing de.cision, while. the. re.maining 37.3% is influe.nce.d by othe.r variable.s that we.re. not te.ste.d in this study. Me.anwhile., product safe.ty and psychological factors did not show a significant e.ffe.ct on the. purchasing de.cision.Conclusion: Product quality, price., packaging, and social e.nvironme.nt have. a positive. and significant e.ffe.ct on the. purchasing de.cision of importe.d orange.s in E.ast Java through purchase. inte.ntion as a me.diating variable.. Me.anwhile., product safe.ty and psychological factors do not have. a significant e.ffe.ct.